1158 Summarising the Reporting of Study Outcomes in Robotic Oesophagectomy: A Systematic Review. (12th October 2021) - Ramirez, J; Jones, C; Gourbault, L; Hurst, W; Abbas, A; Zucker, B; Shah, M; Scroggie, D; ,
Abstract: Introduction: There is an increasing adoption of robotic oesophagectomy in place of standard techniques for oesophageal cancer resection. This is potentially due to its perceived technical benefits and improved short-term outcomes. Consistency in outcome selection, definition and reporting between studies is required for effective evidence synthesis and prevention of research waste. The aim of this review is to perform an in-depth analysis of outcome reporting in robotic oesophagectomy. Method: Systematic searches were conducted using key words for robotic surgery and oesophageal cancer, from inception to February 2020. Studies reporting any outcome for robotic oesophagectomy were included. Outcomes in each study were recorded verbatim and categorised into twelve domains. Outcomes were independently categorised by two reviewers. Where reported, the follow-up period was also recorded. Results: Of 954 abstracts screened, 226 full texts were reviewed and 102 included. Only one study was a RCT. A total of 1422 outcomes were reported. Each study had a median of 14 reported outcomes (range 1-25). Outcomes related to complications (n = 578, 99 studies), technical/operative factors (n = 290, 90 studies), and pathology (e.g., resection margin) (n = 197, 83 studies) were reported most frequently. No single outcome, or outcome domain was reported in all studies. No studies used a core outcome set for reporting. Forty-five studies stated a follow-up period, ranging from <1 month to 58 months. Conclusions: There is significant heterogeneity in the selection and reporting of outcomes in robotic oesophagectomy. This calls for the use of a core outcome set to allow standardisation and transparency of outcome reporting.